2013
DOI: 10.1021/la400422d
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Magnesium Incorporation in the Bulk and Surfaces of Hydroxyapatite

Abstract: We have used a combination of static lattice energy minimization and molecular dynamics simulations to investigate the thermodynamics of Mg incorporation into the bulk and hydrated surfaces of hydroxyapatite (HA). In agreement with recent experimental and theoretical work, our simulations show that the incorporation of low levels of Mg in the Ca (II) site is preferred with respect to incorporation in Ca (I) sites. However, we predict that Mg in the HA bulk material is metastable both with respect to the Mg/Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…251 In addition, their findings also suggested that the incorporation of Mg in the surface rather than bulk led to more stable structure. 251 Matsunga et al 252 investigated divalent substitution in the TCP structure by means of DFT (Figure 5b). As per their obtained results, substitution in β-TCP lattice was more stable than that in the α-TCP lattice.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…251 In addition, their findings also suggested that the incorporation of Mg in the surface rather than bulk led to more stable structure. 251 Matsunga et al 252 investigated divalent substitution in the TCP structure by means of DFT (Figure 5b). As per their obtained results, substitution in β-TCP lattice was more stable than that in the α-TCP lattice.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 98%
“…Contradictorily, an independent study reported the Ca(2) site to be thermodynamically favorable for Mg doping inside the HA lattice . In addition, their findings also suggested that the incorporation of Mg in the surface rather than bulk led to more stable structure . Matsunga et al investigated divalent substitution in the TCP structure by means of DFT (Figure b).…”
Section: Insight Into Phase Stabilitymentioning
confidence: 99%
“…Although Mg 2+ incorporation into the hydrated HAp surface is energetically favorable, Mg 2+ incorporation into bulk HAp is highly unstable, with respect to Mg 2+ /Ca 2+ exchange with the aqueous environment and with respect to separation into Mg-rich phosphate [Mg 3 (PO 4 ) 2 ] and hydroxide [Mg-(OH) 2 ] phases, and hence dependent on crystal growth kinetics. 18 The concentrically arranged, core−shell structure noted for a few of the nodules suggests that their formation may be associated with a calcification center, followed by intermittent growth and inhibition, resulting in a heterogeneous, layered structure. 19 In addition to highly crystalline mineral nodules, the hypermineralized lacuna contains randomly oriented, acicular apatite nanocrystallites.…”
Section: Nano Lettersmentioning
confidence: 99%
“…Homogeneous distribution of magnesium throughout the nodule bulk, higher magnesium content than internodular acicular nanocrystallites, the distinctive rhomboidal morphology, and their single-crystal-like nature all indicate that these structures are not formed by ion-substitution of bone apatite. Although Mg 2+ incorporation into the hydrated HAp surface is energetically favorable, Mg 2+ incorporation into bulk HAp is highly unstable, with respect to Mg 2+ /Ca 2+ exchange with the aqueous environment and with respect to separation into Mg-rich phosphate [Mg 3 (PO 4 ) 2 ] and hydroxide [Mg­(OH) 2 ] phases, and hence dependent on crystal growth kinetics . The concentrically arranged, core–shell structure noted for a few of the nodules suggests that their formation may be associated with a calcification center, followed by intermittent growth and inhibition, resulting in a heterogeneous, layered structure …”
mentioning
confidence: 99%
“…ΔG ideal ≪ WG MeCa . Promising ways for obtaining the enthalpies of formation and the substitution energies are the first-principle calculations [138] and the atomistic modeling [135], [139].…”
Section: Me Aq Ca Apatite Ssmentioning
confidence: 99%